Voltammetric Response of Alizarin Red S-Confined Film-Coated Electrodes to Diol and Polyol Compounds: Use of Phenylboronic Acid-Modified Poly(ethyleneimine) as Film Component - Shigehiro Takahashi; Iwao Suzuki; Takuto Ojima; Daichi Minaki; Jun-ichi Anzai (Sensors, 2018)
Alizarin red S (ARS) was confined in layer-by-layer (LbL) films composed of phenylboronic acid-modified poly(ethyleneimine) (PBA-PEI) and carboxymethylcellulose (CMC) to study the voltammetric response to diol and polyol compounds. The LbL film-coated gold (Au) electrode and quartz slide were immersed in an ARS solution to uptake ARS into the film. UV-visible absorption spectra of ARS-confined LbL film suggested that ARS formed boronate ester (ARS-PBS) in the film. The cyclic voltammetry of the ARS-confined LbL film-coated electrodes exhibited oxidation peaks at −0.50 and −0.62 V, which were ascribed to the oxidation reactions of ARS-PBS and free ARS, respectively, in the LbL film. The peak current at −0.62 V increased upon the addition of diol or polyol compounds such as L-dopa, glucose, and sorbitol into the solution, depending on the concentration, whereas the peak current at −0.50 V decreased. The results suggest a possible use of ARS-confined PBA-PEI/CMC LbL film-coated Au electrodes for the construction of voltammetric sensors for diol and polyol compounds.